Implementasi Pola POAC dalam Manajemen Laboratorium di SMA Kesatuan Bangsa - Ahmi Yofaniar Pratiwi; Rahmat Mulyono (Media Manajemen Pendidikan, 2023)
This study aims to analyze the implementation of the POAC in laboratory management at Kesatuan Bangsa High School. This research is qualitative descriptive and is carried out using observation, documentation, and interview techniques. The results showed that laboratory management at Kesatuan Bangsa High School had implemented the POAC well. The planning function is carried out by the laboratory assistant through the activities of needs analysis, policy determination, budgeting, and activity planning. The organizing function includes the process of delegating tasks and explanation of job descriptions, as well as determining procedures of using the laboratory. The actuating function includes the process of involving teachers in lab equipment and materials management and conducting learning processes in the laboratory. Meanwhile, the controlling function is carried out with an evaluation at the end of each semester by the school principal.